Implementasi Kolaborasi Perguruan Tinggi dengan Komunitas Wisata Mangrove Nanga Sira untuk Peningkatan Kunjungan Wisatawan - Firno Hadi; Suherman Suherman; Abdurrahman Mansyur; Muh. Mahrup Zainuddin Sabari; Riska Julianti Ade Lismula (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The Nanga Sira Mangrove Forest Tourism Area is an ecotourism destination with significant natural potential that has not been utilized optimally. The managing community faces constraints in aspects of digital marketing, educational content development, governance, and supporting facilities. This community service program aims to implement strategic collaboration between higher education institutions and the community to increase tourist visits through a participatory action research approach. The implementation method includes four main stages: observation, participatory planning, activity implementation, and monitoring and evaluation. Core activities conducted include digital marketing training and creative content creation, development of environmental conservation education materials, improvement of tourism governance systems, and physical infrastructure enhancement. Evaluation results show a significant increase in community capacity with a 75% rise in social media interactions and 40% growth in tourist visits over a two-month period. This program successfully proves that the higher education-community collaboration model is effective as a strategy for sustainable tourism development. Recommendations include the importance of continuous mentoring and the development of more innovative tourism packages.